Propuesta de mejora para el proceso de recubrimientos electroestáticos en la empresa Servipintura H&R S.A.S., bajo el modelo de gestión Lean Manufacturing (2021)
This document reports the result of a diagnosis focused on lean manufacturing, which evaluated the degree of maturity or level of compliance of the associated tools, within Servipintura HYR SAS, through specific questions of each methodology, which, valued according to Established criteria, determined a percentage of compliance with each one, allowing to establish a starting point and address the interpretation of the results through the Pareto diagram in order to carry out an action of these represented 80% of affectation to Lean compliance, to In order to be able to define the scope of the study or the most critical tools that should be intervened and thus, have the questions with the lowest score, to analyze and examine them through the method of "the 5 whys", in order to identify the root cause that corrupted or went against the methodology used; Finally, a proposal or improvement action was proposed for each one of them divided into operation, monitoring, control, adaptation and investment activities, establishing the required cost, the persons assigned and the projected time for its development, in order to analyze the investment profitability of the project, through a financial study that finally determined the proposal as viable, according to indicators. Keywords: Lean